Tata Kelola Pembangunan Manusia Oleh Pemerintah Daerah dalam Menekan Ketimpangan Wilayah di Provinsi Sulawesi Selatan - Andi Rahmat Nizar Hidayat; Tri Cahyo Nugroho (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
This study aims to analyze how human development governance is implemented by the Government of South Sulawesi Province in reducing regional disparities, identify institutional factors influencing implementation quality, and examine its implications for human development outcomes. The study employs a qualitative approach using a case study design. Data were collected through interviews with key informants from the Regional Development Planning Agency (Bappeda) and relevant Regional Apparatus Organizations, analysis of regional planning documents such as RPJMD and RKPD, and statistical data from the Central Bureau of Statistics related to the Human Development Index (HDI), poverty, and employment. Data were analyzed thematically using triangulation to ensure validity of findings. The results show that the Human Development Index has been positioned as a key performance indicator in regional development planning documents and prioritized in education and health sector policies. Although overall HDI achievement in South Sulawesi is categorized as high, significant disparities remain across regencies and municipalities, particularly in education and standard of living. A poverty rate of 8.06 percent and the increasing trend of the Gini Ratio indicate that distribution of welfare has not been fully equitable. Furthermore, the dominance of the informal sector in the employment structure reflects challenges related to job quality, income stability, and limited social protection coverage. These findings suggest that the main challenge of human development in South Sulawesi lies not only in improving aggregate indicators but also in strengthening bureaucratic capacity, cross-sectoral coordination, and policy implementation consistency to ensure more inclusive and equitable development across regions.